Pembelajaran Matematika Berbasis Computational Thingking Pada Materi Bangun Ruang - Widiyawati, Selviani; Utari, Fatimah Dwi; Aprinastuti, Christiyanti; Setyaningsih, Tri Wahyu (Smart Education, 2022)
Abstract: Computational Thinking (CT) covers a wide range of cognitive skills that can be expressed in a variety of contexts. This study aims to determine the ability of computational thinking in VB grade students at Kanisius Sorowajan Elementary School through the subject of mathematics in geometrical material. The method used in this research is descriptive with a quantitative approach. The subjects in this study were 25 students of class VB SD Kanisius Sorowajan. Data collection techniques in the form of tests. The data analysis technique is in the form of descriptive analysis. The test instrument is in the form of student worksheets that have been modified by applying the CT foundation. The results of the study revealed that students have very good computational thinking for the foundations of pattern recognition, abstraction and decomposition. Meanwhile, computational thinking with an algorithm foundation is at a good stage. By this it shows students have the knowledge to integrate CT in mathematics. Furthermore, it can be concluded that students have very good computational thinking even though they have never been specifically taught CT subjects.Keywords: geometry, computational thinking, learningAbstrak: Computational Thinking (CT) mencakup beragam keterampilan kognitif yang dapat diekspresikan dalam berbagai konteks. Penelitian ini bertujuan untuk mengetahui kemampuan computational thinking pada kelas VB SD Kanisius Sorowajan mempelajari matematika melalui mata pelajaran geometri. Penelitian ini menggunakan pendekatan deskriptif dan kuantitatif untuk metodologinya. 25 siswa SD VB Kanisius Sorowajan dijadikan sebagai subjek penelitian. Teknik pengumpulan data berupa tes. Analisis deskriptif adalah metode yang digunakan untuk menganalisis data. Instrument tes berupa lembar kerja peserta didik yang telah dimodifikasi dengan menerapkan fondasi CT. Hasil penelitian mengungkapkan bahwa siswa memiliki pemikiran komputasi yang sangat baik untuk fondasi pengenalan pola, abstraksi dan dekomposisi. Sedangkan pada pemikiran komputasi dengan fondasi algoritma pada tahap baik. Dengan ini menunjukkan siswa memiliki pengetahuan untuk mengintegrasikan CT dalam matematika. Selanjutnya dapat disimpulkan bahwa peserta didik memiliki berpikir komputasi yang sangat baik walaupun tidak pernah diajarkan secara khusus mata pelajaran CT.Kata Kunci: Bangun Ruang, Computational Thinking, Pembelajaran